Human papillomavirus persistence or clearance after infection in reproductive age. What is the status? Review of the literature and new data of a vaginal gel containing silicate dioxide, citric acid, and selenite. (June 2021) - Huber, Johannes; Mueller, Anna; Sailer, Manuela; Regidor, Pedro-Antonio
Cervical cancer, the third most common cancer in women, is caused in nearly all cases by a persistent infection with high-risk types of the human papillomavirus. Although human papillomavirus infections are 80%–90% transient and disappear spontaneously within 24 months, human papillomavirus infections that remain are at risk of developing cervical lesions. Different therapeutical approaches have been tested to promote the regression of low-grade lesions or prevent progression. They include the application of 5-fluorouracil, curcumin, imiquimod, interferons, Vitamin D, and others. Also, the effect of probiotics and vaginal therapy with carboxy-methyl-beta glucan was assessed. Review of the literature and presentation of the last study data are presented. Clearance of high-risk human papillomavirus seemed to be promoted by treatment with a new vaginal gel containing a highly disperse SiO2 and an anti-oxidative combination of citric acid and sodium. This gel showed, after 6 months, an improvement of cytological Pap findings (ASC-US, LSIL, ASC-H, or HSIL) in 80.9% of the participants. Similarly, there was a clearing of hr-human papillomavirus in 53% of cases after 3 months of gel administration. The percentage increased slightly in the non-treated control group from 78.3% at baseline to 83% after 3 months. The percentage of patients who were tested positive for p16/Ki67 reduced from 75% at baseline to 5.3% in the treatment group after 6 months, while the percentage decreased only slightly in the non-treated group (baseline: 91.5%; 6 months: 75.2%). The examined vaginal gel may support the healing of conspicuous cytological findings (ASC-US, LSIL, ASC-H, or HSIL) and clearance of hr-human papillomavirus positive results.